Islamic Educational Leadership: The Principal’s Role in Addressing Students' Psychological Impact After Natural Disasters in Indonesia - Utomo, Fajar Hendro; Bafadal, Ibrahim; Timan, Agus; Mustiningsih; Syam, Aldo Redho (LETIGES, 2025)
This paper aims to describe the role of Islamic educational leadership practised by school principals in addressing the psychological impact experienced by students after natural disasters in Indonesia. This article uses a literature study approach that explores information and processing research material through the recording of events that have been reviewed. The role of the principal in Islamic educational leadership is crucial in addressing the psychological impact of natural disasters on students in Indonesia. Principals, guided by Islamic values such as compassion, trust, and justice, are responsible for creating a supportive and safe environment for students affected by trauma. Their leadership involves structured interventions, including phases of stabilization, emotional sharing, and rebuilding trust. Effective communication, resource management, and collaboration with teachers, families, and the community are key to minimizing the long-term psychological effects of disasters. Islamic educational leadership empowers principals to foster resilience and emotional healing, ensuring students' well-being and recovery while maintaining a focus on their academic and personal growth. Limitations are shown in the study of the principal’s role in handling the psychological impact of students as victims of natural disasters within the framework of Islamic educational leadership. This study is grounded in the principles of Islamic educational leadership, emphasizing the importance of compassionate and responsive leadership in managing education during a crisis. It highlights the pivotal role of school principals in guiding and supporting students affected by natural disasters, who require not only academic leadership but also emotional and psychological care rooted in Islamic values.